Herchenefreda. Trzy listy do syna Dezyderego - Chudzikowska-Wołoszyn, Małgorzata (Vox Patrum, 2022)
The present paper contains a translation of three letters written in the first half of the seventh century by the Merovingian aristocrat Herchenefreda to her son Deisider, an influential nobleman and future bishop of Cahors. The translation is preceded by an introduction, in which the reader will find a sketch of the context of the period, information on the lives of Herchenefreda and Dezydier, and the subject matter of the individual letters. The correspondence of the Merovingian authoress eventually found its way into the anonymous history of St. Désider and has thus also been saved from oblivion. It undoubtedly enriches the rich Merovingian epistolary tradition. First of all because of the author herself - a secular noblewoman - who in such a predominant group of her male contemporaries pretends to be a rara avis. Also notable is the personal and emotional tone of the maternal discussed correspondence. The letters are an important testimony to early medieval parental relations, the status of noble matrons, their education, and their duties to their family, husband, sons, and ultimately the entire Christian community.